Musical patterns for comparative epigenomics. Issue 1 (December 2015) - Brocks, David
Abstract Scientific data has been transformed into music in order to raise awareness in the non-scientific community. While the general public is nowadays familiar with the genetic code, there is still a lack of knowledge regarding epigenetic regulation. By making use of the binary nature of the methylome, we here describe a method that transforms methylation patterns into music. The resulting musical pieces show decent complexity and allow the audible recognition between music and underlying methylation state. This approach might therefore facilitate the recognition of complex methylation patterns and increase awareness for epigenetic regulation in the general public.